(untitled) (International Journal of Physiotherapy, 2015)
Background: Task specific training of upper limb may result in learning of new motor task through transfer after repeated practice. Mirror therapy and motor imagery are effective emerging techniques used as an adjunct in rehabilitation of upper limb function in hemiplegia. The purpose of the study is to find comparative effects of task specific motor imagery with mental practice over task specific mirror therapy on upper limb functional activities for subjects with sub acute hemiplegia. Method: An experimental study design with two groups conducted on 30 subjects with sub-acute hemiplegic. Thirty subjects randomised, 15 subjects into group A and 15 into group B. Group A subjects received task specific motor imagery with mental practice thrice a week for 10 weeks and Group B received task specific mirror therapy thrice a week for 10 weeks. In both groups, each session consisted of 60 minutes. The outcome measure such as Action Research Arm Test (ARAT) was measured before and after 10 weeks of intervention. Results: Comparison of post intervention means of ARAT using Independent t test and Mann-Whitney Test showed that there is no statistically significant difference in grasp and gross movement between the groups and there is a statistically significant difference in grip, pinch and total score between the groups. Conclusion: The present study concludes that 10 weeks of task specific motor imagery with mental practice and task specific mirror therapy both shown significant effect on improvement of upper extremity function. However, greater percentage of improvement was found using task specific motor imagery with mental practice in hand function when compared to task specific mirror therapy.